The evaluation of whole-rock and partial leach geochemical exploration techniques applied to the exploration for tanzanite deposits : Merelani, North-Eastern Tanzania - Hansen, Robert N. (Robert Neill) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.